PENGARUH FAMILY TRIPLE SUPPORT (FTS) BERBASIS ATRAUMATIC CARE TERHADAP RESPON NYERI BAYI SAAT IMUNISASI - Sancitha Gupta Putra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Immunization is an attempt to confer immunity in infants and children by taking the vaccine into the body so that it makes antibodies to prevent against certain diseases . Immunization by injections is a procedure that can cause pain and distress to the baby and mother. It is feared will lead to a long- term impact as trauma will experience pain during immunization. The purpose of this study is to examine the effect of Family Triple Support (FTS) on the pain response of the infant when they are having immunization. This study using Pre-experimental design with Intact-Group Comparison. Total sample is 86 respondents, where 43 respondents in control and 43 respondents in intervention groups. Pain was measured by using modified behavior pain scale (MBPS) on respondent’s recorded video. The result shows that intervention group’s mean scores are significantly lower than control group’s where p value = 0,000 (p value<0,05). Recommendations of this study that Family Triple Support (FTS) can be used to reduce the pain response for infants having immunization